Local Buckling Analysis of Free Span for Submarine Pipeline. (2015) - Dong, J.; Chen, X.D.; Wang, B.; Guan, W.H.; Yang, T.C.; Fan, Z.C.
Abstract: Free span resulting from unevenness and scour of seabed often occurs and endanger the safety of submarine pipeline. Local buckling which is an important failure mode for free span should be considered for the safety assessment of pipeline. In this paper, considering the real service status of submarine pipeline, the structural response of free span under loads induced by vortex shedding, effective axial force, gravity and buoyancy was analyzed with numerical simulation and theoretical analysis method. Local buckling analysis for free span with different length was investigated based on the ULS criterion under load controlled condition given by DNV-OS-F101 standard.